Web 2.0 at the Heart of Myanmar’s Turmoil - David Gorombolyi (European Scientific Journal, ESJ, 2022)
As digitalization has transformed arguably all aspects of human existence and co-existence, it has obviously made its way into the realms of politics, diplomacy and the dynamics of emerging social tendencies on all levels – global, regional and local. This study takes a look at how Web 2.0 has affected Myanmar’s public conflicts during the last two decades – and does so from the standpoint of social sciences, examining the unique nature of Burmese online development compared to other parts of the world, analyzing the interrelated nature of civil and government actions in the virtual sphere and on the streets alike. Looking at the related details of recent and partially ongoing social tragedies of Myanmar, this paper shows both how deeply Web 2.0 can infiltrate offline reality, and how obvious its limits are still in the hands of humans.